Survey of Oxygen-rich AGB Stars Using the KVN 4 Receiving Bands—SMASTES. I. - Hyeon Baek; Se-Hyung Cho; Jaeheon Kim; Seung-Min Son; Dong-Hwan Yoon; Kyung-Won Suh (The Astronomical Journal)
Simultaneous observations of 19 H _2 O and SiO maser and thermal lines were performed toward 155 M-type oxygen-rich (O-rich) AGB stars. We used the upgraded four-band (22/43/86/129 GHz) wide receiving system of the Korean VLBI Network (KVN). The 155 O-rich stars composed of 50 semiregulars (SRs), 55 Miras, and 50 OH/IR stars were selected based on previous KVN H _2 O/SiO detected sources. Both H _2 O and SiO masers were detected in 23 stars among 50 SRs, 50 stars among 55 Miras, and 24 stars among 50 OH/IRs, respectively. Out of 50 SRs, H _2 O-only masers, without corresponding SiO maser detection, were observed in four stars. In contrast, no H _2 O-only masers were detected in any of the 55 Mira or 50 OH/IR stars, which differs from the pattern seen with SiO-only masers. Interestingly, in the 50 SRs, the SiO v = 1, J = 2–1 maser was detected more than the SiO v = 1, J = 1–0 maser despite requiring a higher excitation energy. The ^28 SiO v = 0, J = 1–0, 2–1, 3–2 lines were detected more frequently at higher rotational transitions, especially in the SRs and Miras. The HCN and SiS were detected from 11 and 3 stars, respectively. For our observational results, we performed statistical analysis on the intensity ratio variations among H _2 O and various SiO masers, chemical environments, and wind kinematics. The characteristics of these property variations were investigated in the IRAS two-color diagram in relation to their evolutionary stages.